Effects of nanoplastic on cell apoptosis and ion regulation in the gills of Macrobrachium nipponense. (1st May 2022) - Li, Yiming; Liu, Zhiquan; Jiang, Qichen; Ye, Yucong; Zhao, Yunlong
Abstract: Nanoplastic, ubiquitous in aquatic environments, are raising concern worldwide. However, studies on nanoplastic exposure and its effects on ion transport in aquatic organisms are limited. In this study, the juvenile oriental river shrimp, Macrobrachium nipponense, was exposed to five levels of nanoplastic concentrations (0, 5, 10, 20, 40 mg/L) in order to evaluate cell viability, ion content, ion transport, ATPase activity, and related gene expression. The results showed that the apoptosis rate was higher in the high concentration nanoplastic group (40 mg/L) compared to the low concentration nanoplastic group (5 mg/L) and the control group (0 mg/L). The ion content of sodium (Na + ), potassium (K + ), chloride (Cl − ), and calcium (Ca 2+ ) showed a decreasing trend in gill tissue compared to the control group. The Na + K + -ATPase, V(H)-ATPase, Ca 2+ Mg 2+ -ATPase, and total ATPase activities in the gills of M. nipponense showed a general decrease with the increasement of nanoplastic concentration and time of exposure. When increasing nanoplastic concentration, the expression of ion transport-related genes in the gills of M. nipponense showed first rise then descend trend. As elucidated by the results, high nanoplastic concentrations have negative effect on cell viability, ion content, ion transport ATPase activity, and ion transport-related gene expression in the gills of M. nipponense . This research provides a theoretical foundation for the toxic effects of nanoplastic in aquaculture. Graphical abstract: Image 1 Highlights: Polystyrene nanoplastic exposure could restrict cell viability. Polystyrene nanoplastic exposure induced perturbation of ion content in gills of shrimps. Polystyrene nanoplastic exposure could have a negative effect on ion transport ATP enzyme activity. Polystyrene nanoplastic exposure could inhibit ion transport related gene expression.